Critical information security challenges: an appraisal - Shuhaib Mir, Mohammad; Wani , Sharyar; Ibrahim, Jamaludin (2013)
Information is one of the most crucial assets of current day organizations. However, managing this information has become a never ending challenge. Adequate security and privacy are of great essence for information systems containing valuable data and information. Leakage of such information can facilitate large-scale identity theft and successful impersonation of a victim lets the identity thief commit fraud. Identity theft occurs when someone uses another individual’s personal information to pose as that individual. This study highlights the importance of information security management in organizations and identifies various critical security challenges that often lead to information leakage within the organizations. Qualitative method of research has been employed for data collection and analysis. The results obtained are categorized into eleven critical security challenges in order of the number of cases reported for each of them.